RELEVANT DIRECTIONS FOR THE PRODUCTION OF COMPETITIVE CONSTRUCTION PRODUCTS ON THE BASIS OF INNOVATION - T. Yu. Levitskiy (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The article substantiates the necessity for competitive innovative high-tech construction products at the present stage of modernisation of the construction industry and reveals some peculiarities of their manufacture.Methods. In the course of the research, a programme-targeted method was applied, underlying the development of a programme for the innovative development of construction production.Results. Relevant directions of innovative development of construction production are systematised. The world's application experience of a technical regulation parametric model for construction industry product manufacturing is generalised. In order to increase the level of innovative activity of construction organisations, a set of practical measures is proposed whose implementation will ensure the output of competitive building products to the market.Conclusion. Increasing the competitiveness of construction products is closely connected with the activation of innovative processes: the introduction of high technology (including resource-saving) into production processes and the expansion of the output of innovative products with the best consumer properties capable of successfully competing on the market with foreign counterparts in the context of import substitution strategies. The modernisation of the construction industry on the basis of introduction of hightech production methods specifies new requirements to the professional competencies of personnel producing competitive building products. To solve the set problems, a tool for improving the management mechanism of the innovative activity of construction organisations was proposed, ensuring the integration of institutional and production conditions for the large-scale development of advanced technologies and production of science-intensive types of construction products.